IMPROVED LEVEL IN RESILIENCE OF ECOSYSTEM WITH CONSERVATION WATER AREA NETWORK DESIGN, (CASE STUDY OF WEST COAST SOUTH SULAWESI) - Faizal, Ahmad; Rani, Chair; Samawi, Farid (Asian Journal of Aquatic Sciences, 2018)
This study was intended to design network of the conservation areas having high resilience to the environmental changes. Method applied in this study was field survey method, analysis of remote sensing images, and integration of geographical information system (decision support) Marxan Model. Results of this study showed that the western coast of South Sulawesi has biophysical relationships caused by oceanographic influence particularly seawater current and highly supporting the development the network of the conservation areas with regional principle. The optimum value for the establishment of the conservation areas was 66553,13 Ha with protection target of 20% from the available ecosystems